2021
DOI: 10.1007/s10198-021-01416-8
|View full text |Cite
|
Sign up to set email alerts
|

Income level and antibiotic misuse: a systematic review and dose–response meta-analysis

Abstract: Objectives To quantify the association between income and antibiotic misuse including unprescribed use, storage of antibiotics and non-adherence. Methods We identified pertinent studies through database search, and manual examination of reference lists of selected articles and review reports. We performed a dose–response meta-analysis of income, both continuous and categorical, in relation to antibiotic misuse. Summary odds ratios (ORs) and their 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
(49 reference statements)
1
12
1
Order By: Relevance
“…Our study showed that the knowledge and practice of antibiotics use and AMR is significantly dependent on the education level of the respondents which align with the findings of a study done in Lithuania where people with an education level of a college degree and above had better knowledge, more appropriate behaviours, and better practices [46]. Similarly, the level of income was significantly and synonymously associated with the behaviour and practice of antibiotic use in our study which contrasts with a study performed recently but a similar finding was seen in one of the studies in Saudi Arabia [47,48]. The same study demonstrated a significant association between the nature of work and behaviour and practice on antibiotic use like our study where health professionals were better informed about the correct use of antibiotics.…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed that the knowledge and practice of antibiotics use and AMR is significantly dependent on the education level of the respondents which align with the findings of a study done in Lithuania where people with an education level of a college degree and above had better knowledge, more appropriate behaviours, and better practices [46]. Similarly, the level of income was significantly and synonymously associated with the behaviour and practice of antibiotic use in our study which contrasts with a study performed recently but a similar finding was seen in one of the studies in Saudi Arabia [47,48]. The same study demonstrated a significant association between the nature of work and behaviour and practice on antibiotic use like our study where health professionals were better informed about the correct use of antibiotics.…”
Section: Discussionsupporting
confidence: 82%
“… 43 The socio-demographic status of a country has been shown to be associated with HAQ 39 and a small increase in the misuse of antibiotics is observed in middle- and high-income countries. 44 These differences in rates of antibiotic consumption in various countries over time also explain the differing results of our study from other large-scale resistome studies by Hendriksen et al 37 and Munk et al 45 …”
Section: Discussioncontrasting
confidence: 61%
“…According to the Centre for Disease Control, CDC (2019), antibiotic-resistant bacteria have caused at least 2,868,700 infections with 35,900 reported deaths [ 1 ]. The overuse and misuse of antibiotics contribute to the development of these superbugs [ 2 , 3 , 4 , 5 ]. Thus, infectious diseases are harder to treat as antibiotics become less effective, causing damage to the immune system and leading to treatment failure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%